Left Handers in the Right–biased World: An Ethnographie Exploration of Everyday Left–Hander Ineonvenienee. Issue 2 (1st December 2020) - David Tong, Dik Wai
Abstract: This article explores the embodied experiences of handedness‐left and inconvenience in Hong Kong, China. In order to explore left‐hander perceptions of everyday encounters with right‐biased design, young and adult participants were invited to identify the inconveniences that they associate with being left handed. For many respondents, blatant right‐biased design is not remarkably inconvenient; instead, inconvenience is understood to arise from encounters with "neutral handedness." Whereas situations of perceived right‐bias prompt left‐handers to respond with varying degrees of bodily flexibility, inconvenience is experienced in occasions regarded as "hand‐neutral" This paper argues that inconveniences are embedded within and emerge through the body's daily interactions with the wider world. The study's ethnographic findings also problematize the idea of "inconvenience" as an objective phenomenon that indistinctively affects left‐handers.